THE EFFECT OF PROFITABILITY, FREE CASH FLOW, SALES GROWTH, FIRM SIZE ON INDONESIAN DEBT POLICY WITH LIQUIDITY AS MODERATING VARIABLES IN MAIN SECTOR COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE IN 2015-2018 - Yolanda, Yola (Asosiasi Dosen Akuntansi Indonesia, 2020)
This study aims to determine the effect of profitability, free cash flow, sales growth and firm size on corporate debt policy. In addition, this research also tries to prove whether liquidity can be used as a moderator in the research model. This type of research is a quantitative descriptive study. This research was conducted on the Main Sector Companies listed on the Indonesia Stock Exchange in the 2015-2018 period. Sample selection using purposive sampling technique shows that the research sample is 30 companies with a period of 4 years of research, so the number of observations in this study is 120 data. The data analysis method used in this research is Panel Data Regression Analysis which is done with the help of Eviews 9. The results of the study indicate that profitability has a negative and significant effect on debt policy in the main sector companies listed on the Indonesia Stock Exchange. Similarly, free cash flow also has a negative and significant effect. Firm size has a positive and significant influence on debt policy. Whereas liquidity apparently cannot be used as a moderating because it is proven unable to strengthen or weaken the independent variables used in this study.